Influência de promotores químicos na permeação ungueal de tioconazol associado a nanocápsulas poliméricas - Paines, Thamiris Coimbra (2017)
The present study aimed to investigate the influence of two chemical enhancers (N-acetyl-L-cysteine and urea) in the in vitro nail permeation tioconazole associated with polymeric nanocapsules. Each enhancer was added to a nanocapsules suspension at concentrations of 0.5% (w/v) and 5% (w/v) for N-acetyl-L-cysteine and urea, respectively. The suspensions were prepared by the interfacial deposition of pre-formed polymer method and were physico-chemically characterized as the organoleptic characteristics, average diameter of particles, polydispersion index, pH, zeta potential, drug content and encapsuling efficiency. As results, the suspensions presented satisfactory macroscopic characteristics, slightly acid pH , close to neutral, in the case of containing urea, particle size in the nanometric range (186 – 189 nm), polydispersion index ≤0.1; negative zeta potential (-7.5 to -11.9 mV), drug content close to theoretical and encapsulation efficiency around 100%. Suspensions containing urea remained stable during 120 days of storage, while those containing N-acetyl-L-cysteine were stable for seven days. The in vitro release study of tioconazole, conducted by diffusion technique in dialysis bags, demonstrated a release control by the nanocapsules, with respect to the free drug solution, for both formulations. The in vitro nail permeation was evaluated on fragments of human nails using in line cells. As result, it was possible to quantify the drug in receiver medium from the developed formulations and of solutions containing the free drug in the presence of enhancers, obtaining concentrations between 20 and 25 μg / cm2 at the end of the experiment. The amount of tioconazole retained in the nails was calculated. The percentage of drug retained was better from formulations containing N-acetyl-L-cysteine (1,13 ± 0,32), corroborating with the images obtained by SEM, which showed changes in the dorsal surface of nails maintained in contact with the formulations. Such changes were most pronounced for nails treated with N-acetyl-L-cysteine. The in vitro antifungal activity of the formulations was evaluated against C. albicans by method of diffusion in agar with wells. The obtained results showed that the incorporation of tioconazole to the nanostructures did not interfere in its activity, as well as the presence of the enhancers.